Size, Shape, and Protein Corona Determine Cellular Uptake and Removal Mechanisms of Gold Nanoparticles - Ding, Lin; Yao, Chenjie; Yin, Xiaofeng; Li, Chenchen; Huang, Yanan; Wu, Min; Wang, Bin; Guo, Xiaoya; Wang, Yanli; Wu, Minghong (Small (Weinheim an der Bergstrasse, Germany), 2018)
Size, shape, and protein corona play a key role in cellular uptake and removal mechanisms of gold nanoparticles (Au NPs). The 15 nm nanoparticles (NP1), the 45 nm nanoparticles (NP2), and the rod‐shaped nanoparticles (NR) enter into cells via a receptor‐mediated endocytosis (RME) pathway. The star‐shaped nanoparticles (NS) adopt not only clathrin‐mediated, but also caveolin‐mediated endocytosis pathways. However, the 80 nm nanoparitcles (NP3) mainly enter into the cells by macropinocytosis pathway due to the big size. Furthermore, the results indicate that the presence of protein corona can change the uptake mechanisms of Au NPs. The endocytosis pathway of NP1, NP2, and NS changes from RME to macropinocytosis pathway and NR changes from RME to clathrin and caveolin‐independent pathway under the non‐fetal bovine serun (FBS)‐coated condition. Both FBS‐coated and non‐FBS‐coated of five types of Au NPs are released out through the lysosomal exocytosis pathway. The size, shape, and protein corona have an effect on the exocytosis ratio and amount, but do not change the exocytosis mechanism. The systematic study of the endocytosis and exocytosis mechanism of Au NPs with different sizes and shapes will benefit the toxicology evaluation and nanomedicine application of Au NPs. Size, shape, and protein corona play the key role in cellular uptake and removal mechanisms of gold nanoparticles (Au NPs). The uptake mechanisms of five types of Au NPs are different. Size, shape, and protein corona decrease the uptake amount and affect the endocytosis mechanism. However, all of them are released through the lysosomal exocytosis pathway.